Implementing Collaborative Community-based Conservation by Applying Stewardship Contracting in Coastal Marine Systems - Brady, Cullen D (My University, 2019)
On a planet where humans and nature are inextricably connected, solutions to coastal marine conservation problems should incorporate community-based conservation strategies by acknowledging the co-existence of people and nature. Modeled after the United States Forest Service’s stewardship contracting authority and subsequent programs, this thesis proposes a new statutory program, the Community-Based Coastal Zone Restoration Program. This program applies the stewardship contracting terrestrial restoration tool on coastal marine landscapes. This program can address a lack of trust among stakeholders, declining local economic conditions, and need for coastal marine restoration. Integrating stewardship contracting within coastal marine restoration efforts presents an opportunity to encourage ecological, economic, cultural, and social sustainability concurrently. The proposed program does this by incorporating collaborative multi-party engagement in its development, implementation, and monitoring; awarding contracts for restoration work on a best-value end-result basis; authorizes the agency of jurisdiction to trade the value of goods for service; and allows the agency of jurisdiction to retain receipts of excess value to reallocate to additional restoration projects. By leveraging local resources with national or state funds, this program can increase the flexibility in contracting for the restoration of coastal marine systems, build local capacity, and increase local economic and workforce capture.
Thesis (Master's)--University of Washington, 2018
Keywords: Coastal Management; Contracting; Finance; Restoration; Stewardship Contracting; Public policy; Marine affairs